Pengaruh Strategi Learning Start With A Question Terhadap Hasil Belajar Siswa Dalam Bidang Fiqih Di MTS Al-Aman Payaman Solokuro Lamongan - Masyhudi, Ali; Santoso, Subhan Adi (Jurnal Mahasiswa Pendidikan, 2022)
In this study the problems to be discussed are: (1) How is the implementation of the learning start with a question strategy in learning fiqh at MTs Al-Aman Payaman Solokuro Lamongan? (2) How are the student learning outcomes in the field of fiqh at MTs Al-Aman Payaman Solokuro Lamongan? (3) What is the effect of the learning start with a question strategy on student learning outcomes in the field of fiqh at MTs Al-Aman Payaman Solokuro Lamongan? This research is a type of field research that aims to find out whether there is an influence between the x variable and the y variable, while the approach used in this research is a quantitative descriptive study. The data collection method is the method of observation, interviews, questionnaires and documentation. Data analysis techniques to determine the variable x and variable y using the percentage formula and the mean or average value. Meanwhile, to determine the effect between the variable x and the variable y, the researcher used the product moment formula, which then consulted the results on the product moment table. The results showed that the learning start with a question strategy (64.5%) had an influence on student learning outcomes in the field of jurisprudence for class VIII H MTs Al-Aman Payaman Solokuro Lamongan (8.4) where rxy = 0.595 if consulted in the interpretation table, the magnitude is between 0.400 - 0.600, which means it is in the "slightly low" level, while the significant level in the product moment table is 1% = 0.463 and 5% = 0.361 so that ro > rt. So the working hypothesis is accepted and the null hypothesis is rejected.